The Association of High Arousal Threshold with Hypertension and Diabetes in Obstructive Sleep Apnea - Wang, Donghao; Zhang, Yuting; Gan, Qiming; Su, Xiaofen; Zhang, Haojie; Zhou, Yanyan; Zhuang, Zhiyang; Wang, Jingcun; Ding, Yutong; Zhao, Dongxing; Zhang, Nuofu (Nature and science of sleep, 2024)
Compared to low arousal threshold (AT), high AT is an easily overlooked characteristic for obstructive sleep apnea (OSA) severity estimation. This study aims to evaluate the relationship between high AT, hypertension and diabetes in OSA, compared to those with apnea-hypopnea index (AHI). A total of 3400 adults diagnosed with OSA were retrospectively recruited. Propensity score matching (PSM) was conducted to further categorize these patients into the low and high AT groups based on the strategy established by previous literature. The different degrees of AHI and quantified AT (AT score) were subsequently measured. The correlation of AT and AHI with the occurrence of various comorbidities in OSA was estimated by logistic regression analysis with odds ratio (OR). After PSM, 938 pairs of patients arose. The median AT score of high and low AT group was 21.7 and 12.2 scores, and the adjusted OR of high AT for hypertension and diabetes was 1.31 (95% CI = 1.07-1.62, < 0.01) and 1.45 (95% CI = 1.01-2.08, < 0.05), respectively. Compared to low AT score group, the OR significantly increased in patients with very high AT score (30 ≤ AT score), especially for diabetes (OR = 1.79, 95% CI = 1.02-3.13, < 0.05). The significant association was not observed in AHI with increasing prevalent diabetes. Higher AT is significantly associated with increased prevalence of hypertension and diabetes in patients with OSA. Compared with AHI, AT score is a potentially comprehensive indicator for better evaluating the relationship between OSA and related comorbidities.